Leptospirosis With Acute Renal Failure and Vasculitis: A Case Report - Sibel YÜCEL KOÇAK,; Ayşegül KUDU,; Arzu KAYALAR,; Mürvet YILMAZ,; Süheyla APAYDIN, (Archives of Rheumatology, 2019)
Leptospirosis is a zoonotic disease that occurs worldwide. Various clinical manifestations of leptospirosis can be seen. In this article, we present a case with acute renal failure, severe vasculitis and hyperbilirubinemia occurring simultaneously with leptospirosis. A 45-year-old male patient presented with fever, myalgia, jaundice and reddish skin lesions and anuria. Physical examination findings were icteric sclera, large tender hepatomegaly, and lower extremities’ cutaneous necrosis due to vasculitis. Hemodialysis was started. Kidney biopsy revealed degenerative changes of proximal tubules, some of them containing bile casts. Microscopic agglutination test was positive and consistent with leptospirosis. Intravenous ampicillin and oral tetracycline were started. Methylprednisolone 60 mg per day was given for skin vasculitis. Hemodialysis therapy was discontinued. All clinical findings gradually regressed.